What Can Indonesia Learn from American Federalism? - Aleksius Jemadu (Jurnal Administrasi Publik, 2003)
As Indonesia is moving from an authoritarian state to a democratic political system, there is a growing debate whether it is more suitable for the country to adopt a federal system in order to make sure that political power is brought closer to the people in the regions. The paper argues that the American federal system can be a source of some important lessons for Indonesia. However, it is necessary to note that a belief that a federal system may lead to a more equitable distribution of development resources should be read as a theoretical statement rather than an empirical description of reality. After all, some developing countries which adopt federal system like Brazil and Nigeria showed no convincing evidence about a better performance in the national distribution of development resources.